Postoperative Complications Leading to Death after Coagulum Pyelolithotomy in a Tetraplegic Patient: Can We Prevent Prolonged Ileus, Recurrent Intestinal Obstruction due to Adhesions Requiring Laparotomies, Chest Infection Warranting Tracheostomy, and Mechanical Ventilation? - Subramanian Vaidyanathan; Bakul Soni; Gurpreet Singh; Peter Hughes (Case Reports in Urology)
A 22-year-old male sustained C-6 tetraplegia in 1992. In 1993, intravenous pyelography revealed normal kidneys. Suprapubic cystostomy was performed. He underwent open cystolithotomy in 2004 and 2008. In 2009, computed tomography revealed bilateral renal calculi. Coagulum pyelolithotomy of left kidney was performed. Pleura and peritoneum were opened. Peritoneum could not be closed. Following surgery, he developed pulmonary atelectasis; he required tracheostomy and mechanical ventilation. He did not tolerate nasogastric feeding. CT of abdomen revealed bilateral renal calculi and features of proximal small bowel obstruction. Laparotomy revealed small bowel obstruction due to dense inflammatory adhesions involving multiple small bowel loops which protruded through the defect in sigmoid mesocolon and fixed posteriorly over the area of previous intervention. All adhesions were divided. The wide defect in mesocolon was not closed. In 2010, this patient again developed vomiting and distension of abdomen. Laparotomy revealed multiple adhesions. He developed chest infection and required ventilatory support again. He developed pressure sores and depression. Later abdominal symptoms recurred. This patient’s general condition deteriorated and he expired in 2011. Conclusion. Risk of postoperative complications could have been reduced if minimally invasive surgery had been performed instead of open surgery to remove stones from left kidney. Suprapubic cystostomy predisposed to repeated occurrence of stones in urinary bladder and kidneys. Spinal cord physicians should try to establish intermittent catheterisation regime in tetraplegic patients.